2019
DOI: 10.1080/21645515.2018.1559687
|View full text |Cite
|
Sign up to set email alerts
|

Varicella healthcare resource utilization in middle income countries: a pooled analysis of the multi-country MARVEL study in Latin America & Europe

Abstract: Varicella is a mild and self-limited illness in children, but can result in significant healthcare resource utilization (HCRU). To quantify/contrast varicella-associated HCRU in five middle-income countries (Hungary, Poland, Argentina, Mexico, and Peru) where universal varicella vaccination was unimplemented, charts were retrospectively reviewed among 1–14 year-olds. Data were obtained on management of primary varicella between 2009–2016, including outpatient/inpatient visits, allied healthcare contacts, tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…VZV remains latent in sensory ganglia, and its reactivation results in herpes zoster (HZ; shingles) [4,5]. Both varicella and HZ are associated with a significant medical, social, and economic burden on the healthcare system [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…VZV remains latent in sensory ganglia, and its reactivation results in herpes zoster (HZ; shingles) [4,5]. Both varicella and HZ are associated with a significant medical, social, and economic burden on the healthcare system [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Differences could be due to methodological differences, i.e., the granularity used in breaking down cost components or country-specific differences, i.e., healthcare expenditure, income levels, country-specific treatment guidelines, healthcare resource availabilities, and physician practices. 23 Pawaskar et al reviewed the economic burden of varicella in Europe. 8 Average LoS was 4.85 days in high-income countries and 5.89 days in low- and middle-income countries and hospitalization costs accounted for 2% to 21% of total costs, including indirect costs.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a multi-country study (MARVEL) was conducted to assess HCRU and costs associated with varicella in 5 middle-income countries without UVV (Hungary, Poland, Argentina, Mexico, and Peru, 2009–2016) [ 9 ]. That medical chart review study found that varicella was associated with substantial HCRU and financial burden on health systems.…”
Section: Introductionmentioning
confidence: 99%